Superação da dormencia e periodos de armazenamento de sementes de Brachiaria humídicola - Moreira, Alcides Junior Gallo (2014)
The objective of this work indicate the most appropriate method to overcome dormancy in seeds of different periods of Brachiaria humidicola storage. The research was conducted at the Seed Analysis Laboratory of the Faculty of Agricultural Sciences, Federal University of Grande Dourados (UFGD), located in Dourados - MS. Three lots of Brachiaria humidicola seeds were used, collected in the inflorescence (cluster): the first batch of seed was collected in January 2011 and stored for 33 months; the second collected in January 2012, stored for 21 months; the third batch with seeds harvested in January 2013 and stored for nine months. The experimental design was a randomized complete block design with five treatments and four replications. Prior to execution of experiments, we determined the viability of seeds, the tetrazolium test. The assessment of the viability of the seeds was carried out using the criteria set out in the Rules for Seed Analysis (BRAZIL, 2009). The treatments used to overcome dormancy were: control, immersion in sodium hydroxide (NaOH), mechanical scarification, thermal and chemical scarification. Data were statistically analyzed and the means compared by 5% SNK test. With this study we conclude that the use of sulfuric acid in Brachiaria humidicola seeds is not recommended to break dormancy. The mechanical scarification treatments, thermal and with NaOH employment did not promote increase of the germination of the seed. The storage time affects the germination of seeds of B. humidicola.Leaf, and nine months of storage recommended as an ideal time to increase the germination rate.